Mycoplasma Bovis adhesins and their target proteins - Xu, QY.; Pan, Q.; Wu, Q.; Xin, JQ. (Frontiers in Immunology, 2022)
Bovine mycoplasmosis is an important infectious disease of cattle caused by Mycoplasma bovis (M. bovis) which poses a serious threat to the breeding industry. Adhesin is involved in the initial process of M. bovis colonization, which is closely related to the infection, cell invasion, immune escape and virulence of this pathogenic microorganism. For the reason that M. bovis lacks a cell wall, its adhesin is predominantly located on the surface of the cell membrane. The adhesins of M. bovis are usually identified by adhesion and adhesion inhibition analysis, and more than 10 adhesins have been identified so far. These adhesins primarily bind to plasminogen, fibronectin, heparin and amyloid precursor-like protein-2 of host cells. This review aims to concisely summarize the current knowledge regarding the adhesins of M. bovis and their target proteins of the host cell. Additionally, the biological characteristics of the adhesin will be briefly analyzed.